Detection and prevalence of disseminated tumor cells from the bone marrow of early stage male breast cancer patients - Hartkopf, Andreas; Taran, Florin-Andrei; Walter, Christina B.; Hahn, Markus; Fehm, Tanja; Wallwiener, Markus; Brucker, Sara Y. (Breast cancer research and treatment, 2015)
Male breast cancer (mBC) is a rare entity. As detection of disseminated tumor cells (DTCs) in the bone marrow of females with early stage breast cancer is a promising prognostic marker, we aimed to determine the prevalence and prognostic value of DTCs in mBC. Bone marrow aspirates were collected from male patients undergoing primary surgery for early stage breast cancer (T1-4, N0-2, M0) at Tuebingen University, Germany, between January 2001 and April 2015. DTCs were identified by immunocytochemistry (pancytokeratin antibody A45/B-B3) and cytomorphology. 24 patients with mBC were included into the analysis. DTCs were detected in four of these (17 %). There was no significant association between the DTC status and any other clinicopathological parameter. Also, no significant impact of the DTC status on DFS or OS could be observed. DTCs are detectable in patients with early stage mBC. The detection rate is comparable to that in women. No associations between DTCs and clinicopathological features or prognosis were observed, which is most likely due to the small sample size. The detection of DTCs in male patients with early stage breast cancer emphasizes the transmission of future clinical applications for DTCs from women to men.